Relationship between post veraison temperature and the dynamics of anthocyanin development and berry quality in red wine grape (Vitis vinifera) cultivars Shiraz and Cabernet Sauvignon - SHIVASHANKARA, K S; LAXMAN, R H; RAO, N K SRINIVASA; GEETHA, G A; PAVITHRA, K C; PATIL, V S (The Indian Journal of Agricultural Sciences, 2018)
The present investigation was carried out to understand the temperature induced dynamics of berry anthocyanin development and berry quality in wine grape (Vitis vinifera L.) cultivars Shiraz and Cabernet Sauvignon. Temperature variations during fruit maturation period were achieved by altering the pruning dates. Vines were pruned at weekly intervals starting from third or fourth week of October to the end of November. The changes in berry quality parameters such as total soluble solids (TSS), titratable acidity, total anthocyanins, total phenols and total flavonoids were recorded at weekly intervals starting from veraison to harvest. All the quality parameters were significantly higher in early pruned vines of both the cultivars indicating that the best time for pruning to get good quality wine grapes is during the third or fourth week of October. The major quality parameter affected by the temperature during the berry maturation stage was total anthocyanin content. Maximum and minimum temperature (weekly average) during different week from veraison to harvest were recorded. Early pruned vines exposed to a mean day/night temperatures of 30.7°C/14.9°C and 29.6°C/14.1°C in cv. Shiraz and late pruned vines exposed to a mean day/night temperatures of 32.0°C/16.2°C and 32.1°C/16.0°C in cv. Cabernet Sauvignon during 2010 and 2011 respectively. The pattern of anthocyanin development during the berry maturation period (veraison to harvest) indicated that the maximum anthocyanin accumulation was in the second and third week of March; the concentration decreased thereafter irrespective of dates of pruning in both the cultivars during the two years of the study. Correlation coefficients between the skin anthocyanin content and mean maximum and minimum temperatures showed a negative relationship in both the cultivars indicating that the increase in both maximum and minimum temperatures caused a reduction in anthocyanin content at harvest in late pruned vines.